EMBRYONIC VIEWS ON THE FULL-TIME SCHOOL PROGRAM THROUGH THE LENSES OF THE FIELD OF KNOWLEDGE OF PSYCHOANALYSIS (VERUM: Journal of Scientific Initiation, 2024)
This article, fruit of Scientific Initiation Project, promoted within the Center for Research and Scientific Initiation (NUPIC), of the Faculdade Única de Ipatinga (FUNIP), analyzes, from the field of knowledge of Psychoanalysis, the implementation of the full-time school program in Brazil, established by law nº 14.640/2023, which aims to encourage the creation of enrollments in full-time basic education. Through a bibliographical review and documentary analysis of the political texts that circumscribe the aforementioned policy, this production presents the difference between full-time education and integral education, basic experiences and national public policies for full-time education in Brazil, in addition to bringing Psychoanalysis as a new way of reading the articulation between politics and education, arguing, in the end, about the attempt to transform subjects into 'enrolments' and, also, the fantasy of 'improvement' that supports adherence from civil society to the proposal to extend the school day.
Keywords: Full-Time School Program; Full-Time Education; Holistic Education